2014
DOI: 10.1371/journal.pone.0093935
|View full text |Cite
|
Sign up to set email alerts
|

An Ipomoea batatas Iron-Sulfur Cluster Scaffold Protein Gene, IbNFU1, Is Involved in Salt Tolerance

Abstract: Iron-sulfur cluster biosynthesis involving the nitrogen fixation (Nif) proteins has been proposed as a general mechanism acting in various organisms. NifU-like protein may play an important role in protecting plants against abiotic and biotic stresses. An iron-sulfur cluster scaffold protein gene, IbNFU1, was isolated from a salt-tolerant sweetpotato (Ipomoea batatas (L.) Lam.) line LM79 in our previous study, but its role in sweetpotato stress tolerance was not investigated. In the present study, the IbNFU1 g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 72 publications
1
26
0
Order By: Relevance
“…In addition, the systematic up‐regulation of ROS‐scavenging genes was found in the transgenic plants under salt and drought stresses (Figure S8). Our results support that more proline accumulation stimulates ROS‐scavenging system, which leads to the improved salt and drought tolerance in the IbMIPS1 ‐overexpressing sweet potato plants (Liu et al ., ,b).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the systematic up‐regulation of ROS‐scavenging genes was found in the transgenic plants under salt and drought stresses (Figure S8). Our results support that more proline accumulation stimulates ROS‐scavenging system, which leads to the improved salt and drought tolerance in the IbMIPS1 ‐overexpressing sweet potato plants (Liu et al ., ,b).…”
Section: Discussionmentioning
confidence: 99%
“…The BADH gene from spinach improved tolerance to salt, MV‐mediated oxidative and low temperature stresses in transgenic sweet potato (Fan et al ., ). Overexpression of the genes, IbOr , IbLCY‐ Δ, IbNFU1 , IbP5CR , IbMas and IbSIMT1 , from sweet potato enhanced salt tolerance of this crop (Kim et al ., ,b; Liu et al ., ,b,c, ; Wang et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…Plant roots alter their developmental process to rapidly adapt to salt stress. The salt tolerance of sweet potato is improved through increasing betaine, proline and ABA contents, activating ROS scavenging and enhancing myo-inositol biosynthesis, photosynthesis and ion homoestasis29303132454647484950.…”
Section: Discussionmentioning
confidence: 99%
“…The overexpression of IbOr and IbLCY-e genes increased carotenoid accumulation and salt tolerance in transgenic sweetpotato calluses (Kim et al 2013a, b). Wang et al (2013a) isolated IbNFU1 gene from sweetpotato and Liu et al (2014b) found this gene was involved in salt tolerance of sweetpotato. Liu et al (2014a) cloned IbP5CR gene from sweetpotato and the IbP5CR-overexpressing sweetpotato plants exhibited higher salt tolerance.…”
Section: Introductionmentioning
confidence: 99%